(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2025)
This paper explores the paths of communication and its intrinsic relationship with information, as central to the current stage of platform capitalism. We begin by understanding the fields and their importance as organizers and catalysts of contemporary technology, and then analyse the intervention of structures and tools called artificial “intelligence” within digital platforms and their potential consequences for humanity and for the formation of power structures around the world. We present data on the current stage of AI development, as well as data on world hunger and the risks that threaten humanity. Finally, we briefly outline other possible ways of existing. Our process is hermeneutic and is motivated and guided by Ricoeur’s Hermeneutics of Historical Consciousness (2010).